Složitá cesta k inovativní Evropě - Luděk Urban (Charles University in Prague, Institute of Economic Studies (IES), 2007)
– The fact that Europe is lagging behind in comparison with its main competitors in the research and innovation activities is generally known. In 2000 EU countries launching the Lisbon strategy linked with the opening of the European research area were expecting to do away with the remaining barriers between them also in the area of knowledge, technology and research personnel mobility. The paper analyzes research initiatives presented by the Commission, the proposal of the 7th framework programm for research and technological development, the new financial perspective of the EU for the period 2007-2013, the report by an expert group headed by the former Finish prime minister Esko Aho (Creating an Innovative Europe) and finally the follow-up communication of the Commission presenting a broad-based innovation strategy for the EU.
Keywords: O3; O5; 330; Research and development; European Research Area; EU research policy; 7th framework program for research and technological development; innovation strategy; Forschung; Europäische Forschungs- und Technologiepolitik; Innovationspolitik; Innovationswettbewerb; EU-Staaten